Systemic Inflammation and Evidence of a Cardio-splenic Axis in Patients with Psoriasis - Kasper F. Hjuler; Lars C. Gormsen; Mikkel H. Vendelbo; Alexander Egeberg; Jakob Nielsen; Lars Iversen (Medical Journals Sweden, 2018)
The spleen is thought to play a role in atherosclerosis-associated immunity and cardiovascular research has indicated the existence of a cardio-splenic axis. The aim of this study was to assess splenic 18F-fluorodeoxyglucose uptake as a measure of systemic inflammation in patients with untreated psoriasis compared with historical controls assessed by positron emission tomography-computed tomography. Patients with moderate-to-severe psoriasis (n = 12, age 61.4 ± 4.1 years, 83% men, mean  Psoriasis Area Severity Index score of 14.5) and controls (n = 23, age 60.4 ± 4.5 years, 87% men) were included in the study. Splenic inflammation was measured using the background-corrected spleen-liver-ratio (SLR) based on mean standardized uptake values. Mean ± SD SLR was increased in patients with psoriasis compared with controls (0.94 ± 0.11 vs. 0.82 ± 0.08; p = 0.001). SLR was significantly associated with aortic inflammation. These results support the existence of systemic inflammation in patients with psoriasis, and provide the rationale for a mechanistic link between psoriasis-driven inflammation and cardiovascular comorbidity through a spleen-atherosclerotic axis.